2023
DOI: 10.3390/cancers15174304
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Measles–Mumps–Rubella MMR Vaccine Viruses against Glioblastoma

Zumama Khalid,
Simona Coco,
Nadir Ullah
et al.

Abstract: Background: Oncolytic viruses (OVs) have been utilized since 1990s for targeted cancer treatment. Our study examined the Measles–Mumps–Rubella (MMR) vaccine’s cancer-killing potency against Glioblastoma (GBM), a therapy-resistant, aggressive cancer type. Methodology: We used GBM cell lines, primary GBM cells, and normal mice microglial cells, to assess the MMR vaccine’s efficacy through cell viability, cell cycle analysis, intracellular viral load via RT-PCR, and Transmission Electron Microscopy (TEM). Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 86 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The roles of paramyxovirus proteins, including HN and M (NDV) [ 17 , 35 , 36 ], N and P (measles virus) [ 13 , 37 ], M (PPRV) [ 12 ], and V (mumps virus) [ 33 ], in apoptosis or survival of transformed cells have been examined. Although the oncolytic activity of the mumps virus has been previously validated in some studies [ 18 , 30 , 38 40 ], it has been shown that the mumps virus V protein modulates apoptosis in cervical adenocarcinoma cancer cells [ 16 ]. Hence, one question remains whether there is a relationship between tumor cell apoptosis and the expression of other viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of paramyxovirus proteins, including HN and M (NDV) [ 17 , 35 , 36 ], N and P (measles virus) [ 13 , 37 ], M (PPRV) [ 12 ], and V (mumps virus) [ 33 ], in apoptosis or survival of transformed cells have been examined. Although the oncolytic activity of the mumps virus has been previously validated in some studies [ 18 , 30 , 38 40 ], it has been shown that the mumps virus V protein modulates apoptosis in cervical adenocarcinoma cancer cells [ 16 ]. Hence, one question remains whether there is a relationship between tumor cell apoptosis and the expression of other viral proteins.…”
Section: Discussionmentioning
confidence: 99%